2016
DOI: 10.1177/1350650116682161
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influence of plateau roughness and groove texture of honed surface on frictional performance of piston ring–liner system

Abstract: The cylinder liner surface finish, which is commonly produced using the honing technique, is an essential factor of engine performance. The characteristics of the texture features, including the cross-hatch angle, the plateau roughness and the groove depth, significantly affect the performance of the ring pack–cylinder liner system. However, due to the influence of the honed texture features, the surface roughness of the liner is not subject to Gaussian distribution. To simulate the mixed lubrication performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…For example, when texturing the liner with grooves, the effects of groove parameters are opposite for nonflat ring and flat ring. 9 Guo et al 10 textured micro-dimples on the liner of a marine diesel engine and suggested the best depth-to-diameter ratio is 0.1. Even under the poorly lubricated condition, surface textures on liner can also reduce the friction of ring-liner pair.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when texturing the liner with grooves, the effects of groove parameters are opposite for nonflat ring and flat ring. 9 Guo et al 10 textured micro-dimples on the liner of a marine diesel engine and suggested the best depth-to-diameter ratio is 0.1. Even under the poorly lubricated condition, surface textures on liner can also reduce the friction of ring-liner pair.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hu et al [30] studied the mutual influence of the plateau roughness and the groove texture on the frictional performance of PRCL. The effect of plateau roughness is incorporated at a local scale by the homogenized technique while the valley component is considered at a global scale, see Spencer [31].…”
Section: Introductionmentioning
confidence: 99%
“…ICE) has been widely explored by the researchers. [1][2][3][4] On the one hand, the CDA technology is observed to have high fuel economy by reducing the number of the active cylinders and closing the valves under some working conditions. 5,6 Gosala et al 7 investigated the impact of the CDA on the fuel economy of a six-cylinder ICE under low load conditions, the transient engine response for different modes of the CDA was also studied.…”
Section: Introductionmentioning
confidence: 99%